Investigating the microbiome of house dust mites in South Korea - Yi, Myung-hee; Kim, Myungjun; Yong, Tai-Soon; Kim, Ju Yeong (Frontiers in Allergy, 2023)
Understanding the house dust mites (HDMs) microbiome is crucial due to its potential effects on the development of allergic diseases. In 1998, our laboratory collected Dermatophagoides farinae and D. pteronyssinus from beds in a Korean household and began cultivating these HDMs. Our laboratory has been actively investigating several topics about HDMs in recent years, including the bacterial and fungal microbiome and their interactions, as well as the impact of the HDM microbiome on airway inflammation. To study the D. farinae microbiome, we employed high-throughput sequencing of the 16S rDNA amplicons. The results revealed that the two most abundant bacteria were Enterococcus faecalis and Bartonella spp. In contrast, we found almost no bacteria in D. pteronyssinus. By inoculating bacteria to HDMs, we found that D. farinae is more susceptible to bacteria than D. pteronyssinus. This susceptibility was associated with the presence of certain fungal species in D. pteronyssinus. Additionally, we have recently made efforts to produce HDMs with reduced levels of symbiotic bacteria. We believe that standardizing and controlling the microbiome in HDMs are crucial steps for the future development and improvement of allergic immunotherapies.